Ab Initio Molecular Dynamics Simulations and Vibrational Frequency Calculations of Species in Liquid-Liquid Phase Separated MgSO4 Solution at 543 K - Mengzi Zhou; Xiancai Lu; Xiandong Liu; Yingchun Zhang; Xiaoyu Zhang; Kai Wang (Geofluids)
The transport of sulfate-bearing brines is closely relevant to mineralization of sulfide deposits as metal-sulfate complexes exist in hydrothermal fluids. Liquid-liquid phase separation evidently occurs in various metal-sulfate systems with transport and precipitating different from homogeneous fluids. Previous studies have revealed a new species with a Raman peak at ~1020 cm-1 in rich concentration phase of liquid-liquid phase separated MgSO4 solution, and it was interpreted as chain structure polymers. Ab initio molecular dynamics simulations (AIMD) and autocorrelation functions for frequency calculation have been performed to disclose the speciation. The results show that more Mg2+ ions surrounding a SO42- anion lead to higher wavenumber of Raman peaks, which indicates the formation of complicate clusters with ion associations similar to kieserite. Besides, the splitting peaks of v-980 Raman bands at ~980, 990, and 1005 cm-1 in homogeneous solution represent more monodentate Mg-Os (Os: O of SO42-) associations instead of certain species, which favors the formation of prenucleation clusters. Furthermore, bidentate Mg-SO4 ligand is less stable than monodentate ligands at 543 K by applying free energy calculations. Our findings give atomic level recognition of concentrated phase in liquid-liquid phase separated MgSO4 fluids and theoretical explanation of the 980 cm-1 Raman peak shifting, which will further inspire understandings on nucleation processes of hydrated sulfate minerals and Raman spectra resolving of other sulfate systems.